Apie Janinos Degutytės epistoliką, arba Kaip buvo rašomi laiškai - Raškevičiūtė, Jurgita Žana Žana (Literatūra, 2010)
The article considers a poetess’s, Janina Degutytė (1928–1990), epistolary inheritance belonging to Lithuanian literature of the Soviet period (letters written within period of 1955–1988). According to Jurij Lotman, a narrative style of these letters is treated as a “dialect of the memory”. The letter is being analyzed as an everyday talk practice, reflecting the circulation of the appropriate cultural area meanings and a person, writing this letter is considered as a subject being deeply inside the situation, involved in the process of imagination and interpretation.In the article, most attention is paid to the letters of the early period written by the poetess when she was working as a provincial teacher (1955–1958). The article discusses how the communication-interpretation community formed during the period of studies at the Vilnius University of which the members have settled in different Lithuanian villages are able to maintain relations established, describe a new social space and how they are acting inside it. All the community members consider themselves as the cultural world’s representatives appeared in anti-cultural space: being different, they are unable to communicate with a new living environment. The correspondents are acting in a province based on quixotic principle, trying to create the world of their own values. However, in their letters they describe the province as a non-communicative environment, and cultural personal activity – as futile efforts left without any feedback. Therefore, the letter becomes an important means to maintain relations built in the communicative and living world.